And along came Boas : continuity and revolution in Americanist anthropology - Darnell, Regna (Amsterdam studies in the theory and history of linguistic science. Studies in the history of the language sciences ;, 1998)
The advent of Franz Boas on the North American scene irrevocably redirected the course of Americanist anthropology. This volume documents the revolutionary character of the theoretical and methodological standpoint introduced by Boas and his first generation of students, among whom linguist Edward Sapir was among the most distinguished. Virtually all of the classic Boasians were at least part-time linguists alongside their ethnological work. During the crucial transitional period beginning with the founding of the Bureau of American Ethnology in 1879, there were as many continuities as discont.